Formation of Actin Networks in Microfluidic Concentration Gradients - Strelnikova, Natalja; Herren, Florian; Schoenenberger, Cora-Ann; Pfohl, Thomas (Frontiers in Materials, 2016)
The physical properties of cytoskeletal networks are contributors in a number of mechanical responses of cells, including cellular deformation and locomotion, and are crucial for the proper action of living cells. Local chemical gradients modulate cytoskeletal functionality including the interactions of the cytoskeleton with other cellular components. Actin is a major constituent of the cytoskeleton. Introducing a microfluidic-based platform, we explored the impact of concentration gradients on the formation and structural properties of actin networks. Microfluidic-controlled flow-free and steady-state experimental conditions allow for the generation of chemical gradients of different profiles, such as linear or step-like. We discovered specific features of actin networks emerging in defined gradients. In particular, we analyzed the effects of spatial conditions on network properties, bending rigidities of network links, and the network elasticity.